MELTING OF ICE FOR STEFAN PROBLEM USING FINITE DIFFERENCE METHOD - NUR SURIANI, HUSIN (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Stefan Problem exists in heat and mass transfer in objects under phase changes in many physical processes such as solidification of pure metals, freezing of water, deep freezing of foodstuff this is the processes that involve in which phase changes from solid to liquid or vapor states. The object is assumed to undergo a phase change with a moving boundary that has to be tracked as part of the solution. Various numerical methods used for Stefan Problem. We will use Finite Difference Method to solve of Stefan Problem.